Bioinspired Collagen Scaffolds in Cranial Bone Regeneration: From Bedside to Bench - Lee, Justine C. (Adv Healthc Mater, 2017)
Calvarial defects are common reconstructive dilemmas secondary to a variety of etiologies including traumatic brain injury, cerebrovascular disease, oncologic resection, and congenital anomalies. Reconstruction of the calvarium is generally undertaken for the purposes of cerebral protection, contour restoration for psychosocial well-being, and normalization of neurological dysfunction frequently found in patients with massive cranial defects. Current methods for reconstruction using autologous grafts, allogeneic grafts, or allo-plastic materials have significant drawbacks that are unique to each material. The combination of wide medical relevance and the need for a better clinical solution render defects of the cranial skeleton an ideal target for development of regenerative strategies focused on calvarial bone. With the improved understanding of the instructive properties of tissue-specific extracellular matrices and the advent of precise nanoscale modulation in materials science, strategies in regenerative medicine have shifted in paradigm. Previously considered to be simple carriers of stem cells and growth factors, increasing evidence exists for differential materials directing lineage specific differentiation of progenitor cells and tissue regeneration. In this work, we review the clinical challenges for calvarial reconstruction, the anatomy and physiology of bone, and extracellular matrix-inspired, collagen-based materials that have been tested for in vivo cranial defect healing.